Kangaroo Method: Humanized and beneficial strategy for newborns (Research, Society and Development, 2021)
Introduction: The Kangaroo Method is a practice that assists in the prognosis of low birth weight newborns, providing better conditions for bonding with those responsible, stimulating breastfeeding and reducing stress and pain for the newborn. Objective: To describe the importance of the kangaroo method through the art of research and to reveal its benefits for the baby and the guardians. Methodology: This is a study with a qualitative approach, of the integrative review type, whose database was the Virtual Health Library Nursing using the Health Sciences Descriptors (DeCS): Nursing; Kangaroo Method; Maternal and Child. Complete articles were selected, in Portuguese, published between 2016 and 2021. At the end of the application of the criteria, 7 articles emerged for thorough reading and construction of the content. Results: From the reading of the articles, two categories were developed. Category I - Premature babies and the use of the Kangaroo Method Category II- Reality seen by society. Final Considerations: There is a limitation of research in the area chosen to approach the study, however, it was possible to realize the importance of the method in the lives of parents and newborns.